PENGARUH PENGGUNAAN SMARTPHONE SEBAGAI MEDIA PEMBELAJARAN TERHADAP PRESTASI BELAJAR PAI SISWA KELAS VIII SMP NUSA INDAH KECAMATAN SECANGGANG - Rabitah; Ahmad Zaki; Muhammad Saleh (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2023)
The background of this research is that based on the identification carried out by the researchers at the research location, namely: The application of online learning during the Corona Virus Disease-19 pandemic so that Islamic Religious Education teachers must use smartphones as learning media. The objectives of this research are: To determine the effect of using a smartphone as a learning medium on student achievement in the subjects of Islamic Religious Education class VIII Private Junior High School Nusa Indah, Secanggang District. The type of research used in this study is a quantitative research method. In this study the form of the instrument used is in the form of a questionnaire using a Likert scale attitude that has been modified with the following assessments: Strongly agree score 3, Agree score 2, Disagree score 1. The results of this study are: The r_xy value is calculated as 0.379 in The correlation index number above is in the 0.20 – 0.40 group, which means that between Variable X and Variable Y there is a weak or low correlation. This means that the use of Smartphones as a learning medium on the learning achievement of Islamic Religious Education students of class VIII Private Junior High School Nusa Indah Secanggang has a weak correlation